2018
DOI: 10.1111/jcmm.13914
|View full text |Cite
|
Sign up to set email alerts
|

5‐Azacytydine and resveratrol reverse senescence and ageing of adipose stem cells via modulation of mitochondrial dynamics and autophagy

Abstract: Obesity and endocrine disorders have become prevalent issues in the field of both human and veterinary medicine. Equine metabolic syndrome is a complex disorder involving alternation in metabolism and chronic systemic inflammation. It has been shown that unfavourable microenvironment of inflamed adipose tissue negatively affects adipose stem cell population (ASC) residing within, markedly limiting their therapeutic potential. ASCsEMS are characterized by increased senescence apoptosis, excessive accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 67 publications
(77 reference statements)
1
59
0
Order By: Relevance
“…Conversely, cell apoptosis is usually accompanied by abnormal rupture of mitochondria in MSCs. Apoptotic ASCs isolated from equine metabolic syndrome (EMS) horses contain notably increased fragmented mitochondria (Kornicka et al, 2019). Analogously, prominently increased expression of Fis1 and decreased Mfn1 and Mfn2 expression have been reported in apoptotic human umbilical cord MSCs induced by monocrotophos exposure (Srivastava et al, 2018).…”
Section: Mitochondrial Dynamics In Msc Apoptosismentioning
confidence: 84%
See 1 more Smart Citation
“…Conversely, cell apoptosis is usually accompanied by abnormal rupture of mitochondria in MSCs. Apoptotic ASCs isolated from equine metabolic syndrome (EMS) horses contain notably increased fragmented mitochondria (Kornicka et al, 2019). Analogously, prominently increased expression of Fis1 and decreased Mfn1 and Mfn2 expression have been reported in apoptotic human umbilical cord MSCs induced by monocrotophos exposure (Srivastava et al, 2018).…”
Section: Mitochondrial Dynamics In Msc Apoptosismentioning
confidence: 84%
“…Targeted inhibition of Drp1 with mdivi-1 increases mitochondrial fission and protects human PDLSCs against H 2 O 2 -induced cell dysfunction (He et al, 2018). Mdivi-1 treatment rescues the EMS-induced abnormal mitochondrial network in ASCs, which subsequently reverses the senescence of ASCs, as indicated by suppression of p53, p21, and p62 expression (Kornicka et al, 2019). Moreover, short-term or intermittent administration of mdivi-1 is more beneficial for resisting tissue damage (Jheng et al, 2015).…”
Section: Msc-based Mitochondrial Therapeuticsmentioning
confidence: 99%
“…An in vitro study also showed that resveratrol treatment inhibited preadipocyte proliferation, adipogenic differentiation and inflammatory cytokines production in a Sirt1-dependent manner [77]. Other beneficial effects of resveratrol treatment on adipocytes include improving insulin signaling and mitochondrial dynamics [78,79]. Resveratrol plus quercetin upregulated white adipose tissue SIRT1 and SIRT2 in a rat model of sucrose diet-induced metabolic syndrome [80].…”
Section: Treatment Of Metabolic Syndromementioning
confidence: 99%
“…Culturing SVF leads to MSC isolation, and 1-2 week-culture period is needed to produce millions of these fibroblast-like plastic adherent cells known as MSCs [ 6 ]. Autologous SVF extraction procedure replaces any need for allogeneic cell culturing [ 7 ], and therefore risks of contamination, aging of stem cells, or rejection can be avoided [ 8 10 ]. Moreover, the procedure is less expensive.…”
Section: Introductionmentioning
confidence: 99%